2023
DOI: 10.1177/17588359231217966
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 as a potential marker for immunotherapy response prediction in renal cell carcinoma

Qiwen Pan,
Ruiqi Liu,
Xinyue Zhang
et al.

Abstract: Background: Epigenetic mechanisms play vital roles in the activation, differentiation, and effector function of immune cells. The breast and kidney-expressed chemokine (CXCL14) mainly contributes to the regulation of immune cells. However, its role in shaping the tumor immune microenvironment (TIME) is yet to be elucidated in renal cell carcinoma (RCC). Objectives: This study aimed to elucidate the role of CXCL14 in predicting the efficacy of immunotherapy in patients with RCC. Methods: CXCL14 expression and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This possibility is further supported by the association of high CXCL14 expression with better patient survival in multiple cancers, including HNSCC and CxCa [ 41 ]. Furthermore, new evidence from Pan et al has shown that CXCL14 expression is associated with an enhanced response to immunotherapy in renal cell carcinoma [ 67 ]. Additionally, CXCL14 has several beneficial features as a therapeutic agent.…”
Section: Developing Cxcl14 As An Immunotherapeutic Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is further supported by the association of high CXCL14 expression with better patient survival in multiple cancers, including HNSCC and CxCa [ 41 ]. Furthermore, new evidence from Pan et al has shown that CXCL14 expression is associated with an enhanced response to immunotherapy in renal cell carcinoma [ 67 ]. Additionally, CXCL14 has several beneficial features as a therapeutic agent.…”
Section: Developing Cxcl14 As An Immunotherapeutic Agentmentioning
confidence: 99%
“…This could be a key advantage of using CXCL14 compared to other cytokines (e.g., IL-2), many of which have been shown to cause high toxicity or trigger immune suppression via regulatory T cells [ 69 ]. Lastly, CXCL14 has dual functions in enhancing antitumor responses by recruiting natural killer (NK) and T cells into the TME and upregulating MHC-I expression on tumor cells to enhance antigen presentation [ 40 , 42 , 67 ]. Thus, CXCL14 has great potential as an immunotherapeutic agent in novel combination immunotherapy with an ICI, particularly for ICI nonresponders.…”
Section: Developing Cxcl14 As An Immunotherapeutic Agentmentioning
confidence: 99%